NanoTiO2 Sunscreen Does Not Prevent Systemic Oxidative Stress Caused by UV Radiation and a Minor Amount of NanoTiO2 is Absorbed in Humans - Pelclova, Daniela; Navratil, Tomas; Kacerova, Tereza; Zamostna, Blanka; Fenclova, Zdenka; Vlckova, Stepanka; Kacer, Petr (Nanomaterials (Basel, Switzerland), 2019)
The present pilot study tested the efficiency of nanoTiO2 sunscreen to prevent the oxidative stress/inflammation caused by ultraviolet (UV) radiation using biomarkers in subjects' blood, urine, and exhaled breath condensate (EBC). In addition, the skin absorption of nanoTiO2 was studied. Six identical subjects participated in three tests: (A) nanoTiO2 sunscreen, (B) UV radiation, and (C) sunscreen + UV. The first samples were collected before the test and the second after sunscreen application and/or UV exposure. On day 4, the third samples were collected, and the sunscreen was washed off, and the fourth samples were collected on day 11. The following biomarkers were measured: malondialdehyde, 4-hydroxy-trans-hexenal, 4-hydroxy-trans-nonenal, aldehydes C6-C12, 8-iso-Prostaglandin F2α, o-tyrosine, 3-chlorotyrosine, 3-nitrotyrosine, 8-hydroxy-2-deoxyguanosine, 8-hydroxyguanosine, 5-hydroxymethyl uracil, and leukotrienes, using liquid chromatography-electrospray ionisation-tandem mass spectrometry. Titania was measured using inductively coupled plasma mass spectrometry and TiO2 nanoparticles by transmission and scanning electron microscopy. Sunscreen alone did not elevate the markers, but UV increased the biomarkers in the plasma, urine, and EBC. The sunscreen prevented skin redness, however it did not inhibit the elevation of oxidative stress/inflammatory markers. Titania and nanoTiO2 particles were found in the plasma and urine (but not in the EBC) in all sunscreen users, suggesting their skin absorption.
Keywords: exhaled breath condensate (EBC); inflammation; nanotoxicology; nanoparticles absorption; oxidative stress; urine; transmission electron microscopy (TEM); sunscreen; UV irradiation; nanoTiO2; plasma; scanning electron microscopy (SEM)